(untitled) (Global Journal of Science Frontier Research, 2023)
Globalization has facilitated the rapid increase in informal employment and has been associated with the generation of employment that is flexible precarious and insecure Many informal jobs are not only flexible precarious and insecure but are also hazardous and take place in unhealthy and unsafe environments Informal sector workers operate in inhumane conditions and makeshift places without sanitary facilities The cost in human terms of the existence of the informal sector and ways in which it is sustained is tragic Enforcement and compliance with safety and health standards are unknown There are high and tragic incidences of occupational related accidents and injuries that go unabated in Kampala The purpose of the study was to assess compliance levels of occupational safety and health OSH measures among informal manufacturing sector workers in Kampala Uganda A cross sectional survey design was used both qualitative and quantitative data were collected Three hudred and eighty eight 388 firms were sampled among the manufacture of metal products furniture textiles and clothing concrete and brick paper and paper recycling repair of machinery and other manufacturing sectors of the informal sector Data on hazards and practices were obtained using questionnaires and International Labour Organization ILO adapted workplace checklistwith a response rate of 92 secondary data got fromOSH Conventions Acts textbooks and government reports Data was analyzed into frequencies and percentages Various types of hazards were identified inadequate ventilation 50 4 optical radiation 44 extreme weather 37 4 extreme heat 34 3 extreme noise 27 9 in manufacture of metal products Noxious gases 26 7 and paints 19 5 in furniture and metal products while sharps 21 3 were in manufacture of metal products Ergonomic hazards heavy lifting 19 5 in metallic products and psychosocial hazards such as stress accounted for 30 5 in metal products Compliance with OSH control measures was low however Personal Protective Equipment PPE usage was 65 4 and 61 6 applying OSH control measures in the informal sector Creation of awareness through mass media training and awareness provision of OSH regulations and regulation by government were recommended